Clinical features and prognosis of thymic neuroendocrine tumours associated with multiple endocrine neoplasia type 1: A single‐centre study, systematic review and meta‐analysis. (16th October 2017) - Ye, Lei; Wang, Weixi; Ospina, Naykky Singh; Jiang, Lei; Christakis, Ioannis; Lu, Jieli; Zhou, Yulin; Zhu, Wei; Cao, Yanan; Wang, Shu; Perrier, Nancy D.; Young, William F.; et al.
Summary: Objective: Thymic neuroendocrine tumour (TH‐NET) accounts for almost 20% of multiple endocrine neoplasia type 1 (MEN1)‐associated mortality. Identifying risk factors for the development of these rare tumours and prognostic factors for clinical outcomes will be helpful in clinical practice. Design and Patients: We performed a retrospective analysis of patients treated for TH‐NET associated with MEN1 in a single institution and meta‐analysis of literature reports. We used a fixed effect model to pool results across studies to evaluate the prevalence, clinical features and prognosis. Results: TH‐NET was detected in 9 (7.4%) of 121 patients with MEN1 seen in our institution, and 5 (55.6%) were women. Seven additional studies were identified through a systematic review of the literature. The pool estimate of TH‐NET prevalence was 3.7% (n = 99) in MEN1 (n = 2710), sex ratio was 79:20 (male vs female), and the median age at diagnosis was 43.0 years (range, 16.0‐72.0 years). Forty‐three patients died with a median survival time of 8.4 years. Older age at diagnosis (HR = 1.4, 95% CI = 1.0‐1.8, P = .03), maximum tumour diameter (HR = 1.5, 95% CI = 1.0‐2.3, P = .04) and presence of metastasis (HR = 1.6, 95% CI = 1.0‐2.5, P = .04) were associated with worse outcome. A male predominance (91.9% vs 59.5%, P < .001) and history of smoking (59.0% vs 23.5%, P = .015) were more common in American/European series compared to Asian reports. Conclusion: TH‐NET is a rare but fatal component of MEN1. Earlier detection of TH‐NET in patients with MEN1 may be recommended which should theoretically result in better outcomes. Different genetic backgrounds (race) appear to result in clinical difference.